Psychometric Properties of the Independent and Interdependent Self-Construal Questionnaire: Evidence From the Czech Republic - Lacko, David; Čeněk, Jiří; Urbánek, Tomáš (Frontiers in Psychology, 2021)
This article introduces a validation study of the Czech version of an independent and interdependent self-construal questionnaire (SCS, Vignoles et al., 2016) conducted on 330 Czech subjects. The results suggest satisfactory reliability in most SCS subscales (α = .651 –⁠ .855, ω = .661 –⁠ .854) and sufficient convergent validity with the INDCOL questionnaire. However, its factor structure is unsatisfactory (RMSEA = .053 [.048, .057], SRMR = .080, CFI = .775, TLI = .755). The article also critically discusses the shortcoming of the Czech and original versions of the questionnaires and the general issues of the individualism-collectivism construct in the cross-cultural context as a whole.